2020
DOI: 10.1016/j.tips.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FGF21 for the Treatment of Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH), the severe stage of nonalcoholic fatty liver disease (NAFLD), is defined as the presence of hepatic steatosis with inflammation and hepatocyte injury and different degrees of fibrosis. Although NASH affects 2-5% of the global population, no drug has been specifically approved to treat the disease. Fibroblast growth factor 21 (FGF21) and its analogs have emerged as a potential new therapeutic strategy for the treatment of NASH. In fact, FGF21 deficiency favors the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 70 publications
(85 reference statements)
3
47
0
Order By: Relevance
“…It has also been pointed out that increased FGF21 circulating levels in over-nutrition could show the presence of compensatory responses by FGF21 to the underlying metabolic stress [ 70 ]. Additionally, FGF21 has direct anti-inflammatory and antifibrotic effects on the liver that are not associated with insulin resistance and obesity [ 71 , 72 ]. Thus, the absence of differences in this marker could also be due to the fact that patients only present liver steatosis and not steatohepatitis which implies inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been pointed out that increased FGF21 circulating levels in over-nutrition could show the presence of compensatory responses by FGF21 to the underlying metabolic stress [ 70 ]. Additionally, FGF21 has direct anti-inflammatory and antifibrotic effects on the liver that are not associated with insulin resistance and obesity [ 71 , 72 ]. Thus, the absence of differences in this marker could also be due to the fact that patients only present liver steatosis and not steatohepatitis which implies inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…ALS rather selectively affects upper and lower motor neurons, leading to a loss of motor control and muscle wasting. Approximately 10% of ALS cases are familial, while the remaining 90% of cases are sporadic indicating there is no clear inheritance pattern ( Zarei et al., 2015 , 2020 ). The first gene found to be associated with ALS was superoxide dismutase 1 ( SOD1 ), and mice engineered to overexpress the G93A- SOD1 ( SOD1 G93A ) mutation develop motor neuron disease similar to human ALS ( Gurney et al., 1994 ; Rosen et al., 1993 ; Ticozzi et al., 2011 ; Tu et al., 1996 ; Turner and Talbot, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that ChREBP potently transactivates expression of the metabolic hormone FGF21, and FGF21 is under investigation as a therapeutic for treatment of NAFLD (87,91,(96)(97)(98)(99)(100). FGF21 protects against fructose-induced liver fibrosis, which might support a protective role for ChREBP in the pathogenesis of NAFLD (96).…”
Section: Lipid Homeostasis In Chrebp Loss-of-function Modelsmentioning
confidence: 83%